2019
DOI: 10.1108/ijse-06-2019-0377
|View full text |Cite
|
Sign up to set email alerts
|

Subjective social class and individual preferences for redistribution

Abstract: Purpose The recent increase in economic inequalities in many countries heightened the debates about policy preferences on income distribution. Attitudes toward inequality vary greatly across countries and numerous explanations are offered to clarify the factors leading to support for redistribution. The purpose of this paper is to examine the link between subjective social class and redistributive demands by jointly considering the individual and national factors. The author argues that subjective measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…In accordance with previous research, the scores were reversed such that a higher score indicates stronger support for redistribution. This score has been adopted by previous international comparative studies on support for redistribution (Duman, 2020; Sealey and Handy, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with previous research, the scores were reversed such that a higher score indicates stronger support for redistribution. This score has been adopted by previous international comparative studies on support for redistribution (Duman, 2020; Sealey and Handy, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Subjective social class identification can be understood as an individual's perception of their position within a hierarchy relative to others (Duman, 2020; Harrits & Pedersen, 2018; Kraus et al., 2009). How individuals perceive their social position depends not only on what they view as objective characteristics, but it also relies on how they experience society and how they perceive their current and future positions in comparison with others (Lindemann, 2007).…”
Section: Defining and Measuring Social Classmentioning
confidence: 99%
“…Most people identify as members of the middle class and tend to place themselves toward the center of the social hierarchy in cross‐national studies, regardless of the specific measure used (Duman, 2020; Evans & Kelly, 2004). National studies on New Zealand (Haddon, 2015), England (McGovern & Nazroo, 2015), Germany (Präg, 2020), Poland (Trappmann et al., 2017), Denmark (Harrits & Pedersen, 2018), Korea (Kim et al., 2018b), and Canada (Genest‐Grégoire et al., 2019; Livingstone &, Scholtz, 2016) also show a strong preference for identifying as middle class.…”
Section: Social Class Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, personal evaluations of living standards and expectations about income might better capture the subtle aspects of social status (Operario et al, 2004). It has been found that subjective class positions are explanatory for redistributive preferences even after controlling for objective indicators such as income, education, and labor market status (Duman, 2019). If more individuals in an economy consider themselves as materially deprived and suppose that their income prospects would not get better, they would become more hostile towards outgroup members.…”
Section: Figure 1 Unemployment Rates and Subjective Job Loss Risk Across Countriesmentioning
confidence: 99%